Incidence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in North Carolina from December 2020 – February 2022 - Elyse M. Miller; Ross M. Boyce; Aaron M. Kipp; L Kristin Newby; Christopher W. Woods; Caitlin A. Cassidy; Annika K. Gunderson; C Suzanne Lea; Coralei E. Neighbors; Bonnie E. Shook-Sa; Richard Sloane; Anne P. Starling; et al. (PLoS ONE, 2025)
Background Surveillance estimates of SARS-CoV-2 infections over time have relied on mandatory clinician and laboratory reporting. These estimates increasingly underestimated true viral incidence due to asymptomatic infections, variable access to testing, and self-administered diagnostics. To overcome these limitations, the North Carolina Department of Health and Human Services partnered with academic researchers to conduct three concurrent population-based longitudinal cohort studies in three distinct North Carolina counties to offer more accurate estimates of the incidence, prevalence, and vaccination rates for SARS-CoV-2. Methods We enrolled and followed adult residents of three North Carolina counties from August 2020-February 2022. Demographic and health information was collected in biweekly surveys. Nasal swabs were collected biweekly and tested for SARS-CoV-2 using PCR testing. Blood samples were collected monthly and tested for antibodies to the SARS-CoV-2 nucleocapsid and spike proteins. We calculated monthly seroprevalence, sero-incidence, PCR test positivity, and vaccination uptake. Results We enrolled 646 participants. Routine blood samples and nasal swab samples were contributed by 639 and 642 participants, respectively. By February 2022, 98% (95% CI: 97.4–98.2) had antibodies to the SARS-CoV-2 spike protein, and 13% (95% CI: 12.4–14.2) had antibodies to the nucleocapsid protein, indicating viral exposure. PCR testing detected infection among 14% (95% CI: 13.1–15.0) of participants, but cumulative PCR test positivity was only 1.3% (95% CI: 1.2–1.4). Over half of PCR-detected infections were asymptomatic. By February 2022, 97% of participants had completed the primary vaccine series, and 52% had received a booster dose. Conclusions Nearly all participants had anti-SARS-CoV-2 antibodies by the end of follow-up, primarily through vaccination. The incidence of PCR-detected infections was similar to antibody testing, but PCR test positivity substantially underestimated incident infections. These findings emphasize the importance of prospective infection monitoring via antibody testing in a comprehensive approach to tracking viral infections in the community setting.